Response of ants, beetles and spiders to disturbance varies among taxa in a South African savannah biome - Mavasa, Risuna; Yekwayo, Inam; Mwabvu, Tarombera; Tsvuura, Zivanai (African Entomology, 2023)
Savannahs are structurally complex ecosystems consisting of a diverse community of plants and animals such as arthropods. Arthropods are essential in many ecosystem processes that help maintain life on Earth. The anthropogenic conversion of natural landscapes into croplands, residential and industrial areas has a negative impact on surface-active arthropods that have limited dispersal abilities and narrow habitat preferences. This study investigated the effect of disturbance on assemblages of ants, beetles and spiders in the savannah vegetation in Mpumalanga province, South Africa. We compared species richness, abundance and composition of these three taxa between the pristine savannah and the savannah that is exposed to a variety of anthropogenic activities (disturbed savannah). Arthropods were collected using pitfall traps in 15 sites in pristine savannah and 15 sites in disturbed savannah. We found that disturbance affects species richness and abundance of these taxa differently. Disturbance did not affect species richness of spiders and abundance of beetles, while greater species richness of ants and beetles, as well as abundance of ants and spiders was in disturbed than in pristine savannah. Furthermore, the species compositions of all taxa were different between disturbed and pristine savannah. The disturbed savannah had twice more unique indicator species than the pristine savannah. Differences in assemblages of arthropods between pristine and disturbed habitats suggest that it may be important to consider habitats in and outside protected areas in the conservation of arthropods, particularly in areas with greater percentage of natural and semi-natural landscapes occurring outside protected areas.